Current Advances and Prospects in Carbon Nanomaterials-based Drug Deliver Systems for Cancer Therapy - Lai, Chunmei; Li, Linyan; Luo, Bangyue; Shen, Jiangwen; Shao, Jingwei (Current Medicinal Chemistry, 2023)
The in-depth intersection between nanoscience and oncology comes from the fact that nanomaterials are in a similar dimension to basic biomolecules. Drug delivery systems (DDSs), which are either targeted to a particular site or intended for the controlled release in a particular position, have been studied extensively at the nanoscale and are, by far, the most advanced technology in the area of nanoparticle applications. This, consequently lead to the improvement and development of convenient administration routes, lower toxicity, fewer side effects, and extended drug life cycle. Carbon nanomaterials (CNMs) with favorable size and unique fluorescence properties, which was considered an ideal candidate to transport or deliver therapeutic drugs to specific targets in a controlled manner. The development of DDSs based on them constitutes an interesting topic in highly effective and universal therapies to achieve better therapeutic outcomes and reduce the side effects of malignancies. In this review, the cutting-edge progress of CNMs in DDSs was comprehensively summarized. Additionally, the emphasis was placed on the applications of CNMs including fullerene, graphene, carbon nanotubes (CNTs), carbon dots (CDs), and nano-diamonds (NDs) in drug delivering. Further, we gave some insights into the future direction and foreseeable challenges of DDSs based on CNMs used in cancer therapy, which we hope these inspirations in DDSs associated with anti-cancer therapy will provide perspectives in designing new drugs for further tumor treatment.
Keywords: drug delivery